RELASI CINTA DALAM TASAWUF - Suwito, Suwito (Fakulta Ushuluddin dan Humaniora Universitas Islam Negeri Walisongo Semarang, Indonesia, 2013)
Abstract: This article discusses the relationship of love in the Sufi perspective. Opositorum Coindencia theory is used to dissect this relationá¹¢ip , so that the devil Sufism is seen as a